Tools to evaluate medication management for caregivers of people living with dementia: A systematic review - Melissa Gench; Mouna J. Sawan; Aili Langford; Danijela Gnjidic (Wiley, 2021)
Abstract Background Caregivers often undertake medication management for people living with dementia without formal training. There is a need to evaluate caregiver medication management practices for people living with dementia to identify and address the key issues that contribute to caregiver burden. Objectives This study aimed to identify and summarize approaches that evaluate medication management for caregivers of people living with dementia and appraise caregiver's involvement in aspects of medication management. Search Strategy A systematic search was undertaken in five databases: Medline, Embase, PsycINFO, Scopus and International Pharmaceutical Abstracts. Studies written in English that contained tools and surveys that evaluated aspects of medication management for caregivers of PWD were included. Results A total of 10 studies were included. Medication selection was assessed in six studies, supply and monitoring/review was captured in seven studies, with administration assessed in nine studies. Caregivers were commonly involved in decision‐making for medication changes (77.1%-86.8%) and in the ordering (55.9%-86.0%) and collection (87.0%-92.4%) of medications. Reported caregiver involvement in medication administration showed a wide range (44%-94.7%) between the studies. Challenges in administration were commonly related to polypharmacy and dosage regimen complexity. Conclusions Current tools capture specific aspects of medication management, with medication administration the most evaluated aspect of medication management. Future research is needed to develop a tool to holistically evaluate the complexities of medication management for caregivers of people living with dementia to minimize adverse events at transitions of care. Public Contribution From the authors' previous research, caregivers highlighted the need to address key issues in medication management for people living with dementia.